2015
DOI: 10.1111/jace.13931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Current Flow During the Sintering of Zirconium Diboride by Field Assisted Sintering Technology

Abstract: Effect of electric current on sintering behavior and microstructure evolution of zirconium diboride (ZrB2) was investigated using three different configurations of Field Assisted Sintering Technology/Spark Plasma Sintering. The current flow through the ZrB2 compact was controlled by modifying the interface between the graphite punches and the electrical conductive powder. Boron nitride discs, graphite foils or direct contact with the graphite punches were the three different interfaces used in order to deflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Recall that the formation of secondary h‐BN phase is one of the few phases that can be formed during SPS consolidation, particularly at temperatures higher than 1800°C. Other phases such as metal carbides, boron carbide, or layered graphite phases can be formed in situ during SPS . These secondary phases will affect the flexural strength of specimens subjected to SPS to a certain extent, but also can be used as pinning phases to control the grain size of consolidated ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…Recall that the formation of secondary h‐BN phase is one of the few phases that can be formed during SPS consolidation, particularly at temperatures higher than 1800°C. Other phases such as metal carbides, boron carbide, or layered graphite phases can be formed in situ during SPS . These secondary phases will affect the flexural strength of specimens subjected to SPS to a certain extent, but also can be used as pinning phases to control the grain size of consolidated ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…In their paper examining spark plasma sintering of zirconium diboride, Gonzalez-Julian et al showed that the use of graphite discs often placed between the ceramic sample and the graphite punches in spark plasma sintering can cause a reduction in current flow though the specimen [45]. The largest currents are obtained when the ceramic is pressed directly against the graphite to which the power supply is connected, giving samples with the highest density and largest grain size [45]. However this risks adhesion of the sample to the graphite bars, which is usually avoided by the use of the graphite foil which can be more easily ground off after heat treatment.…”
Section: Electrical Contactmentioning
confidence: 99%
“…However there is scope to remove some of these disadvantages. For example, Gonzalez-Julian et al [45] demonstrated that for field-assisted densification of ZrB2 in conventional SPS moulds, where the maximum current is permitted to pass though the sample during heat treatment, the density is maximised. Using a modified SPS set-up where the sample is insulated from the graphite die walls using an insulating alumina tube inside the die, similar to the setup described by Zapata-Solvas et al [32], thus forcing the current to flow through the sample rather than through the die walls, may more fully realise the advantages of the flash sintering setup within an SPS configuration.…”
Section: Zirconium Diboridementioning
confidence: 99%
“…Electrically insulating phases are often used in SPS to direct current flow, albeit, at a meso or macroscale 19 . As the SPS processing of the nanocomposite powder commences, the porous WC-Co-ND agglomerates deform, and the ND films on the surface inhibit current flow, which thereby hinders heat transfer and solid state diffusion.…”
Section: Discussionmentioning
confidence: 99%